(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
FDI may be defined as an investment involving a lastinginterest and control by an investor who is a resident of another economy, otherthan that of the host economy. In the simple sense, FDI implied that theinvestor has a significant degree of influence on the management. ForeignDirect Investments are investments made by residents of one economy with theobjective of establishing a lasting interest in a company located in anothereconomy (host economy). FDI refers tothe purchase by the citizens of one country of non-financial assets in anothercountry. Foreign direct investment involves the acquisition or establishment ofa firm, company or enterprise in a country outside of the registered corporatehome country. FDI in real estate involves acquisition of land or buildingacross all commercial, residential and retail segments. Any constructionactivity is also included in FDI.